2021
DOI: 10.5811/westjem.2020.10.48887
|View full text |Cite
|
Sign up to set email alerts
|

First Pass Success Without Adverse Events Is Reduced Equally with Anatomically Difficult Airways and Physiologically Difficult Airways

Abstract: Introduction: The goal of emergency airway management is first pass success without adverse events (FPS-AE). Anatomically difficult airways are well appreciated to be an obstacle to this goal. However, little is known about the effect of the physiologically difficult airway with regard to FPS-AE. This study evaluates the effects of both anatomically and physiologically difficult airways on FPS-AE in patients undergoing rapid sequence intubation (RSI) in the emergency department (ED). Methods: We analyzed prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Even in a recent consensus paper on PHAAM quality indicators, the threshold to terminate an attempt remains undefined and will need further clarification to improve future studies and their interpretations. One solution could be combining FPS with avoiding adverse events for a more clinically relevant variable, as used in some recent studies [ 35 , 37 , 38 ]. Our results also displayed a significant difference in on-scene time between FPS and non-FPS groups.…”
Section: Discussionmentioning
confidence: 99%
“…Even in a recent consensus paper on PHAAM quality indicators, the threshold to terminate an attempt remains undefined and will need further clarification to improve future studies and their interpretations. One solution could be combining FPS with avoiding adverse events for a more clinically relevant variable, as used in some recent studies [ 35 , 37 , 38 ]. Our results also displayed a significant difference in on-scene time between FPS and non-FPS groups.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our study has limitations with the incomplete patientlevel data that may help us truly interpret the physiologic hypoxemia and cardiovascular instability are not normally consequences of airway management, they may complicate physiologically difficult intubation 5 and many COVID patients who fail noninvasive ventilation due to progressive disease fall into that category. Existing evidence suggests that first-pass success may not distinguish between anatomical and physiologically difficult airways, 6 further limiting the ability of the first-pass success metric to detect cardiorespiratory consequences of COVID-19 airway management.…”
Section: Emergency Airway Management In Covid-19: Replymentioning
confidence: 99%
“…Other evidence does not support the protective benefits of the ramp position for obese patients; Pacheco et al . showed that anatomically difficult airways were associated with a reduced ‘FPS without AEs’ rate 30 . Although obesity itself was included in the anatomically difficult category, it was not shown to be independently associated with a change in ‘FPS without AEs’ in the regression model.…”
Section: Discussionmentioning
confidence: 91%
“…showed that 94.9% of trauma patients presented an anatomically difficult airway, likely due to deformity and obstruction of the airway. Supine positioning can exacerbate these difficult airways, further supporting the use of bed tilt in these patients 30 …”
Section: Discussionmentioning
confidence: 92%